Atypical Forms of Employment in the Slovak Republic - Silvia TRELOVA (Communications of International Proceedings, 2020)
The issue of flexibility in employment relations means an agreement between the employer and the employee, and this is beneficial for both of these subjects of employment relations. One of the manifestations of the effect of flexibility in labour law is the possibility to perform work through flexible employment relations, also referred to as atypical employment relationships. Atypical forms of employment include all forms of employment that are not the employment relationship for a determined weekly working time (full-time) and for an indefinite period. This article analyzes individual atypical forms of work, which are enshrined in the legislation of the Slovak Republic and clarifies the application of the relevant provisions in practice.
Keywords: atypical forms of employment; fixed-term employment relationship; part-time employment; job sharing; homework; telework.